ÁLVAREZ VÉLEZ, M.ª Isabel y VIDAL PRADO, Carlos (coords.) (2018). La Constitución Española: 1978-2018. Madrid: Lefebvre-El Derecho (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2018)
Recensión de la obra: ÁLVAREZ VÉLEZ, M.ª Isabel y VIDAL PRADO, Carlos (coords.) (2018). La Constitución Española: 1978-2018. Madrid: Lefebvre-El Derecho.